2016
DOI: 10.1590/1806-9282.62.07.622
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of acute appendicitis in pregnant versus non-pregnant women: A comparative study

Abstract: ArAs A et Al. 622rev assoC med bras 2016; 62(7):622-627 ORIGINAL ARTICLEThe diagnosis of acute appendicitis in pregnant versus non-pregnant women: A comparative study Objective: To investigate whether the diagnosis of acute appendicitis is affected by pregnancy or not. Method: A retrospective study with the analysis of the medical records of all women suspected of having appendicitis who underwent appendectomy at our hospital between June 2010 and March 2015 were reviewed. The patients were divided into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Currently, the main surgical technique in the management of acute appendicitis during pregnancy is yet to be established. The preferred surgical method is based upon the trimester of pregnancy and the surgeon's own preference (3,9,13,24). Our findings indicated that the laparoscopic management of appendicitis was more frequently used in the non-pregnant women than in the pregnant women.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Currently, the main surgical technique in the management of acute appendicitis during pregnancy is yet to be established. The preferred surgical method is based upon the trimester of pregnancy and the surgeon's own preference (3,9,13,24). Our findings indicated that the laparoscopic management of appendicitis was more frequently used in the non-pregnant women than in the pregnant women.…”
Section: Discussionmentioning
confidence: 80%
“…It has been reported that the preoperative diagnosis of appendicitis can be difficult during pregnancy. Anatomical and physiological changes in pregnancy may make the diagnosis more uncertain and delay the treatment of appendicitis (3,5,10,14,18). While nausea and vomiting occur frequently during pregnancy, rebound tenderness and guarding are not often seen in pregnant women with appendicitis due to the shift of the appendix upward and laterally as the uterus grows, which results in diminished response to peritoneal irritation (9,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…underdiagnosis in pregnant patients results in perforation and peritonitis, which leads to unfavorable complications of early delivery, miscarriage, fetal loss, and maternal mortality. [4] This study presented aims, first of all, compare demographic, biochemical and histopathological features of pregnant and non-pregnant female patients admitted to our surgery clinic instruction with an initial diagnosis of AAp. The second aim is to present maternal and fetal complication following appendectomy among pregnant patients.…”
Section: Introductionmentioning
confidence: 99%